A prospective ascertainment of cancer incidence in sub‐Saharan Africa: The case of Kaposi sarcoma. (28th January 2016) - Semeere, Aggrey; Wenger, Megan; Busakhala, Naftali; Buziba, Nathan; Bwana, Mwebesa; Muyindike, Winnie; Amerson, Erin; Maurer, Toby; McCalmont, Timothy; LeBoit, Philip; Musick, Beverly; Yiannoutsos, Constantin; et al.
Abstract: In resource‐limited areas, such as sub‐Saharan Africa, problems in accurate cancer case ascertainment and enumeration of the at‐risk population make it difficult to estimate cancer incidence. We took advantage of a large well‐enumerated healthcare system to estimate the incidence of Kaposi sarcoma (KS), a cancer which has become prominent in the HIV era and whose incidence may be changing with the rollout of antiretroviral therapy (ART). To achieve this, we evaluated HIV‐infected adults receiving care between 2007 and 2012 at any of three medical centers in Kenya and Uganda that participate in the East Africa International Epidemiologic Databases to Evaluate AIDS (IeDEA) Consortium. Through IeDEA, clinicians received training in KS recognition and biopsy equipment. We found that the overall prevalence of KS among 102, 945 HIV‐infected adults upon clinic enrollment was 1.4%; it declined over time at the largest site. Among 140, 552 patients followed for 319, 632 person‐years, the age‐standardized incidence rate was 334/100, 000 person‐years (95% CI: 314–354/100, 000 person‐years). Incidence decreased over time and was lower in women, persons on ART, and those with higher CD4 counts. The incidence rate among patients on ART with a CD4 count >350 cells/mm 3 was 32/100, 000 person‐years (95% CI: 14–70/100, 000 person‐years). Despite reductions over time coincident with the expansion of ART, KS incidence among HIV‐infected adults in East Africa equals or exceeds the most common cancers in resource‐replete settings. In resource‐limited settings, strategic efforts to improve cancer diagnosis in combination with already well‐enumerated at‐risk denominators can make healthcare systems attractive platforms for estimating cancer incidence. Abstract : Estimation of incidence is fundamental to cancer epidemiology but poses considerable challenges in resource‐limited settings. In East Africa, we demonstrate how a focused effort to improve cancer diagnosis in combination with an already well‐enumerated at‐risk denominator made a healthcare system‐based population fertile ground for estimating the incidence of Kaposi sarcoma (KS). We show that the overall incidence of KS in HIV‐infected adults far exceeds the incidence of the most common cancers in resource‐rich settings.